The transcription factor sry‐related HMG box‐4 (SOX4) is required for normal renal development in vivo. Issue 6 (29th April 2013) - Huang, Jez; Arsenault, Michel; Kann, Martin; Lopez‐Mendez, Carlos; Saleh, Monique; Wadowska, Dorota; Taglienti, Mary; Ho, Jacqueline; Miao, Yuan; Sims, David; Spears, Jonathan; Lopez, Alfonso; et al.
<x xml:space="preserve">Abstract</x> Background: The DNA‐binding transcription factor Wilms' Tumor Suppressor‐1 (WT1) plays an essential role in nephron progenitor differentiation during renal development. We previously used Wt1 chromatin‐immunoprecipitation coupled to microarray (ChIP‐chip) to identify novel Wt1 target genes that may regulate nephrogenesis in vivo. We discovered that all three members of the SoxC subfamily, namely, Sox4, Sox11, and Sox12, are bound by Wt1 in mouse embryonic kidneys in vivo. SoxC genes play master roles in determining neuronal and mesenchymal progenitor cell fate in a multitude of developmental processes, but their function in the developing kidney is largely unknown. Results: Here we show that all three SoxC genes are expressed in the nephrogenic lineages during renal development. Conditional ablation of Sox4 in nephron progenitors and their cellular descendants (Sox4nephron‐ mice) results in a significant reduction in nephron endowment. By postnatal day (P)7, Sox4nephron‐ renal corpuscles exhibit reduced numbers of Wt1+ podocytes together with loss of expression of the slit diaphragm protein nephrin. Sox4nephron‐ mice develop early‐onset proteinacious glomerular injury within 2 weeks of birth progressing to end‐stage renal failure within 5–9 months. Conclusions: Collectively, our results demonstrate an essential requirement of Sox4 for normal renal development in vivo. Developmental Dynamics 242:790–799, 2013. © 2013 Wiley Periodicals, Inc.